Handbook of pathophysiology. - Lazenby, Ramona Browder; Corwin, Elizabeth J. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
'This pathophysiology handbook is ideally suited for easy reference in the classroom or clinical environment. The book presents a summary of physiology concepts for each body system, followed by an overview of important pathophysiology concepts related to'alterations' in that body system. These pathophysiology concepts provide the necessary foundation for understanding the disease or injury states that are presented next in the chapter'--Provided by publisher.
(Publisher-supplied data) Cell Structure and Function -- Genetics -- Cancer -- The Immune System -- The Integument -- Homeostasis and the Stress Response -- Neuroendocrine-Immune Interaction -- The Nervous System -- The Endocrine System -- The Musculoskeletal System -- The Senses -- The Hematologic System -- The Cardiovascular system -- The Respiratory System -- The Gastrointestinal System -- The Pancreas and Diabetes Mellitus -- The Liver -- The Genitourinary System -- Fluid and Electrolyte and Acid-Base Balance -- The Reproductive System.
Rev. ed. of: Handbook of pathophysiology / Elizabeth J. Corwin. 3rd ed. c2008.
Includes bibliographical references and index.
Keywords: Pathologic Processes -- Handbooks; Physiological Phenomena -- Handbooks